Bacterial Subversion of Autophagy in Cystic Fibrosis - Flores-Vega, Verónica Roxana; Vargas-Roldán, Silvia Yalid; Lezana-Fernández, José Luis; Lascurain, Ricardo; Santos-Preciado, José Ignacio; Rosales-Reyes, Roberto (Frontiers in Cellular and Infection Microbiology, 2021)
Cystic fibrosis (CF) is a genetic disease affecting more than 70,000 people worldwide. It is caused by a mutation in the cftr gene, a chloride ion transporter localized in the plasma membrane of lung epithelial cells and other organs. The loss of CFTR function alters chloride, bicarbonate, and water transport through the plasma membrane, promoting the production of a thick and sticky mucus in which bacteria including Pseudomonas aeruginosa and Burkholderia cenocepacia can produce chronic infections that eventually decrease the lung function and increase the risk of mortality. Autophagy is a well-conserved lysosomal degradation pathway that mediates pathogen clearance and plays an important role in the control of bacterial infections. In this mini-review, we describe the principal strategies used by P. aeruginosa and B. cenocepacia to survive and avoid microbicidal mechanisms within the autophagic pathway leading to the establishment of chronic inflammatory immune responses that gradually compromise the lung function and the life of CF patients.